2021
DOI: 10.1016/j.ebiom.2021.103352
|View full text |Cite
|
Sign up to set email alerts
|

VB10, a new blood biomarker for differential diagnosis and recovery monitoring of acute viral and bacterial infections

Abstract: Background: Precise differential diagnosis between acute viral and bacterial infections is important to enable appropriate therapy, avoid unnecessary antibiotic prescriptions and optimize the use of hospital resources. A systems view of host response to infections provides opportunities for discovering sensitive and robust molecular diagnostics. Methods: We combine blood transcriptomes from six independent datasets (n = 756) with a knowledgebased human protein-protein interaction network, identifies subnetwork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…, and Ravichandran et al. have earlier shown that a similar network approach is capable of identifying condition-specific perturbations that are biologically relevant and thus useful for biomarker discovery ( Sambarey et al., 2017b ; Metri et al., 2017 ; Ravichandran et al., 2021 ). Briefly, our method uses a knowledge-based comprehensive human protein–protein interaction network (hPPiN) previously constructed by us ( Table S2 A), renders it specific to each given condition by integrating gene expression data into it, and sensitively mines most perturbed subnetworks and their most influential epicentric nodes ( Sambaturu et al., 2016 , 2021 ; Ravichandran and Chandra, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…, and Ravichandran et al. have earlier shown that a similar network approach is capable of identifying condition-specific perturbations that are biologically relevant and thus useful for biomarker discovery ( Sambarey et al., 2017b ; Metri et al., 2017 ; Ravichandran et al., 2021 ). Briefly, our method uses a knowledge-based comprehensive human protein–protein interaction network (hPPiN) previously constructed by us ( Table S2 A), renders it specific to each given condition by integrating gene expression data into it, and sensitively mines most perturbed subnetworks and their most influential epicentric nodes ( Sambaturu et al., 2016 , 2021 ; Ravichandran and Chandra, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a ‘suspected coinfection’ diagnosis was made by the attending physicians based on the clinical parameters (PCT, CRP, TLC, NLR or ESR). The clinical parameters were considered suggestive of bacterial coinfection at the following thresholds - PCT ≥ 0.25 ng ml −1 , 10 CRP ≥ 10 mg dl −1 , 11 TLC ≥ 12 500 cells per μl, 9 NLR ≥ 12.5, 12 and ESR ≥ 60 mm h −1 . 9 Since all the patients were culture-negative, they were classified into 3 categories of different confidence in clinical diagnosis based on these parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical parameters were considered suggestive of bacterial coinfection at the following thresholds - PCT ≥ 0.25 ng ml −1 , 10 CRP ≥ 10 mg dl −1 , 11 TLC ≥ 12 500 cells per μl, 9 NLR ≥ 12.5, 12 and ESR ≥ 60 mm h −1 . 9 Since all the patients were culture-negative, they were classified into 3 categories of different confidence in clinical diagnosis based on these parameters. If 3 or more parameters were suggestive of bacterial infection, the diagnosis of bacterial coinfection is of higher confidence and therefore the patients were classified as ‘probable bacterial coinfection’.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations